AN EVALUATIVE ANALYSIS OF TPACK-BASED NAHWU TEACHING MATERIALS ORIENTED TOWARD HIGHER-ORDER THINKING SKILLS - Noza Aflisia; Raisha Febyola; Karima Tussa’diah (Al Ibrah: Journal of Arabic Language Education, 2026)
This study aims to evaluate the pedagogical characteristics, strengths, and limitations of Higher-Order Thinking Skills (HOTS)-oriented Nahwu teaching materials developed within the Technological Pedagogical Content Knowledge (TPACK) framework in Arabic language learning. The study employed a qualitative library research design using descriptive-evaluative content analysis. The teaching materials were analyzed based on several indicators, including pedagogical organization, contextuality of content, technology integration, HOTS orientation, integration of Islamic values and local wisdom, and accessibility aspects. The findings reveal several pedagogical strengths, particularly in the simplified presentation of Nahwu rules, the use of contextual Arabic texts, the integration of Islamic and local cultural values, gender-balanced representation, the utilization of digital media, and the implementation of HOTS-oriented activities. However, the analysis also identifies several limitations, including dependence on internet connectivity and the absence of empirical validation regarding instructional effectiveness. This study concludes that the analyzed teaching materials possess considerable potential to support contextual and technology-based Arabic language learning while also promoting the development of Higher-Order Thinking Skills. Nevertheless, further empirical investigation and pedagogical refinement are still required to enhance their inclusiveness and instructional effectiveness.